(untitled) (Actual Problems of Psychology in Educational Institutions, 2023)
The article is devoted to the analysis of the comprehensive problem of the development of communicative behavior of schoolchildren of adolescent and youth age. The characteristics of the sociolect of modern youth are considered. The scientific argumentation of the necessary polymodality of the study of sociocultural predictors of the development of communicative strategies of the behavior of adolescents and youth in the dialogic educational space is presented. The results of the empirical measurement of the communication direction of teenagers and young men are presented. It was established that the orientation of schoolchildren in the period of adulthood in the coordinates “I — Other” has a mainly monologic vector. It has been statistically confirmed that the differences in the detection of personality orientation in communication between schoolchildren studying in secondary education institutions of different types are statistically insignificant, these characteristics in the compared groups differ only quantitatively. It is emphasized that the results of the empirical study indicate the insufficiency of purposeful influence in educational institutions regarding the development of a variable communicative dialogic culture of schoolchildren and a dialogic model of professional interaction in the “Teacher — Student” system without disturbing the professional-communicative balance. It is noted that the introduction of a dialogue system in education is an essential factor in the development of the personal potential of each participant in the educational process.